Tingkat Intrusi Air Laut di Wilayah Pesisir Kecamatan Kuta Utara, Badung - Manuaba, I Nyoman; Sugianto, Made Agus (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: Seawater intrusion in North Kuta District, Badung Regency, has become a serious threat due to excessive groundwater exploitation, groundwater subsidence, and tourism activities. Previous research showed a decline in groundwater quality and expansion of seawater intrusion. This study aims to map the distribution of seawater intrusion in 2024 and predict its spread until 2029 in order to provide mitigation recommendations. Research methods: The study used the Audio Magnetotelluric (ADMT) and geoelectric methods at 15 track points, as well as groundwater quality tests in 32 wells with TDS, DHL, chloride, pH, salinity, and hardness parameters. The data were analyzed using the Surfer program for mapping the distribution of intrusion, and the prediction of the spread rate was calculated through regression analysis based on historical data. Findings: Distribution of Intrusion 2024 low-moderate category occurred in Canggu and Tibubeneng Villages (resistivity 4.5–15 ohm.m; TDS 700–10,000 mg/L), while the high-level category was identified in Kerobokan Kelod Village (resistivity <4.5 ohm.m; TDS 10,000–20,000 mg/L) with a stretch of 1,200 meters on the coast and 700 meters inland. In 2029, intrusion is predicted to spread inland at a rate of 35–56 meters/year, especially in Kerobokan Kelod, due to increased chloride and decreased water quality. Implication: Seawater intrusion has the potential to cause health problems (e.g. urolithiasis) and threaten the sustainability of water resources. Therefore, it is necessary to limit groundwater extraction, strengthen the PDAM network, and conserve aquifers.